Modification of polyethylene glycol with choline chloride and evaluation of the CO2 absorption capacity of their aqueous solutions - Sadeghpour, Mahsa; Yusoff, Rozita; Aroua, Mohamed Kheireddine; Tabandeh, Mojtaba (Wiley, 2017)
In this study, two new water-soluble poly ionic liquids (PILs) polyethylene glycol- Di choline chloride (PEG-(ChCl)2) were modified, with two molecular weights of PEG, 400 and 600, to be used as solvents for CO2 capture. The modified polymers were characterized using Fourier transform infra-red (FT-IR) spectroscopy and proton nuclear magnetic resonance (1H-NMR). CO2 absorption using the PILs was conducted at temperatures from 30 to 70°C and at pressures ranging from 10 to 13 bars. Both PILs saturated and then regenerated under the regeneration temperature: 90–100°C. The results showed that most of CO2 in the liquid phase is released through the thermal regeneration before solutions start to boil after three cycles. PEG (400)–(ChCl)2, and PEG(600)–(ChCl)2 with a concentration of 0.03M showed CO2 loading of 16.24 and 15.68, respectively. These results were 25% higher than the original PEG (400–600).